COMMUNITY-BASED SLEEP HEALTH PROMOTION DURING CAR-FREE DAY: A PUBLIC EDUCATION INITIATIVE BY THE INDONESIAN SOCIETY OF SLEEP MEDICINE (PERDOKTIN) - Irwan Triansyah; Yanti Fitri Yasa; Putri Sari Ivanny; Ade Teti Vani (Nusantara Hasana Journal, 2026)
Sleep is a fundamental determinant of physical, mental, and social well-being. However, inadequate sleep duration, poor sleep quality, and unhealthy sleep habits remain common and often unrecognized public health problems. Limited awareness of sleep health contributes to delayed recognition of sleep disorders and increases the risk of chronic diseases and reduced quality of life. This community service program aimed to improve public awareness of healthy sleep through community-based education during the Car-Free Day event in Padang City, Indonesia. A descriptive community-based health promotion approach was implemented on 5 April 2026 by the Indonesian Society of Sleep Medicine (PERDOKTIN). The program included public education on adequate sleep duration and quality, sleep hygiene counseling, interactive discussions, and a Fun Walk campaign to disseminate key messages on healthy sleep behaviors. Program implementation was documented through field observations and participant engagement. The activities attracted enthusiastic community participation and generated active discussions regarding healthy sleep practices and common sleep disorders. Participants demonstrated increased awareness of the importance of maintaining adequate sleep duration, good sleep quality, and healthy sleep habits. The Fun Walk campaign further enhanced public engagement and increased the visibility of PERDOKTIN's sleep health promotion initiatives. Community-based sleep health promotion conducted during Car-Free Day is a practical and effective approach to improving sleep health literacy. Similar educational initiatives should be expanded to strengthen preventive healthcare and promote healthier communities.